THE STRATEGIES OF HUMOR MATERIAL CREATION: TRANSITIVITY ANALYSIS (STRATEGI PENCIPTAAN MATERI HUMOR: ANALISIS TRANSITIVITAS) - Rawuh Yuda Yuwana (UIN Raden Mas Said Surakarta, 2019)
The purpose of this research was to find out strategies in creating Indonesian humour materials. This research is a descriptive-qualitative research. In collecting the data, the researcher used listening technique by taping and writing. In analyzing data, this research applied equalizing reference method by comparing technique to support codification, reduction, presentation, and interpretation such as work design of qualitative research. As the result of this research, it has been found 8 strategies in creating Indonesian humour materials, namely: (1) exploiting the common truth that people already know, (2) changing constituents with his language experience, (3) putting false pronouns deliberately, (4) conveying something incomplete, (5) diverting different languages, (6) providing an unrelated response at all, (7) exploiting the language gap to distort its meaning, and (8) conveying something unnatural, absurd, even impressed controversy.